PERBANDINGAN Cr-51 (III) DAN Cr-S1 (VI) ANORGANIK PADA HASIL IRADIASI Cr(CO)s DAN Cr(C5H7O2)3 DENGAN NEUTRON TERMAL - Sunarhadijoso Soenarjo; Said Adam; Iswandi Idris (Jurnal Kimia Terapan Indonesia, 1992)
Thermal neutron irradiation on Cr(CO)6 and Cr(C5H7O2)3 target compounds had been conducted with an average neutron flux of about 2.8 x 10(12) n.cm(-2).der(1). Both post-irradiated target compounds gave inorganic radiochromium in oxidation states of +3 and +6 which were separated by solvent extraction method: For radioactivity measurement, the trivalent species was separased from the hexavalent by hydroxide precipitation using K2CrO4 and Cr(NO)3. 9H2O carriers. The inorganic chromium content was chemically determined by spectrophotometric method without adding arry carriers. The activity of the trivalent inorganic chromium produced from Cr(CO)6 irradiation was higher than that of the hexavalent ones, but in the case of Cr(C5H7O2)3 irradiation; the activity of the hexavalent species was higher. In both cases, the specific activity of the trivalent species was higher than that of the hexavalent species. The specific activity of total inorganic chromium obtained from the irradiation of Cr(CO)6 was higher than that of Cr(C5H7O2)3.